2022
DOI: 10.1371/journal.pgen.1010274
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ChvG-ChvI regulon by cell wall stress confers resistance to β-lactam antibiotics and initiates surface spreading in Agrobacterium tumefaciens

Abstract: A core component of nearly all bacteria, the cell wall is an ideal target for broad spectrum antibiotics. Many bacteria have evolved strategies to sense and respond to antibiotics targeting cell wall synthesis, especially in the soil where antibiotic-producing bacteria compete with one another. Here we show that cell wall stress caused by both chemical and genetic inhibition of the essential, bifunctional penicillin-binding protein PBP1a prevents microcolony formation and activates the canonical host-invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…7A ). This mode of regulation has been documented for other cell envelope stress response TCSs in α-proteobacteria ( 94 - 97 ).…”
Section: Discussionsupporting
confidence: 53%
“…7A ). This mode of regulation has been documented for other cell envelope stress response TCSs in α-proteobacteria ( 94 - 97 ).…”
Section: Discussionsupporting
confidence: 53%
“…The absence of AmpD in A. tumefaciens leads to the accumulation of muropeptide intermediates (anhydro‐MurNac and MurNac‐linked muropeptide) in the cytoplasm and a subsequent increase in beta‐lactamase activity (Figueroa‐Cuilan et al., 2022; Gilmore & Cava, 2022). Beta‐lactam sensitivity has been observed in the absence of AmpC or its regulator AmpR (Figueroa‐Cuilan et al., 2022) and upon alterations in cell‐wall remodeling (Williams et al., 2022). We had made the striking observation that the absence of LsrB caused severe beta‐lactam antibiotic sensitivity as if AmpC was absent (Eisfeld et al., 2021) and wondered how LsrB, which had not previously been linked to cell‐wall remodeling or antibiotic resistance, was implicated in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, various other cell envelope perturbations can also potentiate the signal: for example, cell wall stress resulting from inhibition of the essential penicillin-binding protein PBP1a has recently been shown to activate the ExoS-ChvI pathway (Williams et al, 2022), and JspA's LysM domain, predicted to bind peptidoglycans, was shown to be critical for protection against the antimicrobial peptide NCR247 (Arnold et al, 2017). This model can accommodate a number of scenarios for how JspA and LppA jointly respond to envelope stress: for instance, LppA may enable the proper folding or positioning of JspA in the membrane, or misfolding of LppA may directly induce JspA's proteolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, conditions that specifically trigger the ExoR-ExoS-ChvI pathway in S. meliloti remain elusive (Bélanger et al, 2009;Keating, 2007;Ratib et al, 2018), and different cues for divergent species are possible. Furthermore, some cues may directly activate the ExoS sensor kinase and bypass ExoR: recent studies indicate that peptidoglycan stress induces the A. tumefaciens ChvG-ChvI system independently of ExoR (Williams et al, 2022), and that in S. meliloti, membrane disruption due to a phosphatidylcholine deficiency activates ExoS without a concomitant decrease in steady-state levels of ExoR (Geiger et al, 2021). In the free-living alphaproteobacterium Caulobacter crescentus, which lacks an ExoR ortholog, the ChvG-ChvI system was shown to be stimulated by various stresses, including DNA damage, acidic pH, osmotic upshift, and inhibition of cell wall synthesis (Frohlich et al, 2018;Quintero-Yanes et al, 2022;Stein et al, 2021).…”
Section: Introductionmentioning
confidence: 99%